The application of specific point energy analysis to laser cutting with 1 μm laser radiation - Hashemzadeh, M.; Suder, W; Williams, S.; Powell, J.; Kaplan, A.F.H.; Voisey, K.T. (Elsevier, 2014)
Specific point energy (SPE) is a concept that has been successfully used in laser welding where SPE and power density determine penetration depth. This type of analysis allows the welding characteristics of different laser systems to be directly compared. This paper investigates if the SPE concept can usefully be applied to laser cutting. In order to provide data for the analysis laser cutting of various thicknesses of mild steel with a 2kW fibre laser was carried out over a wide range of parameter combinations. It was found that the SPE concept is applicable to laser cutting within the range of parameters investigated here.